Oxide-free hybrid silicon nanowires: From fundamentals to applied nanotechnology - Bashouti, Muhammad Y.; Sardashti, Kasra; Schmitt, Sebastian W.; Pietsch, Matthias; Ristein, Jürgen; Haick, Hossam; Christiansen, Silke H. (Progress in Surface Science, 2013)
The ability to control physical properties of silicon nanowires (Si NWs) by designing their surface bonds is important for their applicability in devices in the areas of nano-electronics, nano-photonics, including photovoltaics and sensing. In principle a wealth of different molecules can be attached to the bare Si NW surface atoms to create e.g. Si-O, Si-C, Si-N, etc. to mention just the most prominent ones. Si-O bond formation, i.e. oxidation usually takes place automatically as soon as Si NWs are exposed to ambient conditions and this is undesired is since a defective oxide layer (i.e. native silicon dioxide-SiO 2) can cause uncontrolled trap states in the band gap of silicon. Surface functionalization of Si NW surfaces with the aim to avoid oxidation can be carried out by permitting e.g. Si-C bond formation when alkyl chains are covalently attached to the Si NW surfaces by employing a versatile two-step chlorination/alkylation process that does not affect the original length and diameter of the NWs. Termination of Si NWs with alkyl molecules through covalent Si-C bonds can provide long term stability against oxidation of the Si NW surfaces. The alkyl chain length determines the molecular coverage of Si NW surfaces and thus the surface energy and next to simple Si-C bonds even bond types such as CC and CC can be realized. When integrating differently functionalized Si NWs in functional devices such as field effect transistors (FETs) and solar cells, the physical properties of the resultant devices vary. © 2013 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2013.nat.dphy.IAP.exphys.oxidef
Keywords: Field effect transistors; Heterojunction; Hybrid functionalization; Silicon nanowire; Solar cells